Sistem Informasi Pendidikan - Maryamah Maryamah; Lias Hasibuan; Kasful Anwar; Ahmad Fadhil Rizki Ahmad (Milenial: Journal for Teachers and Learning, 2021)
An information system is a system within an organization that meets the needs of daily transaction processing that supports managerial organizational functions with the strategic activities of an organization to be able to provide certain external parties with the reports that are presented. In the world of education, information systems that are closely related are the use of information technology such as the internet which can help provide information to the public easily. There are two groups of approaches in defining a systems approach that applies to its components or elements. And the component approach defines the system as a collection of elements that can be relied upon to achieve a certain goal. The information environment consists of 3, namely: 1). Data, 2). Information, and 3). Knowledge. In the world of education, these three environments have covered everything. So the information system becomes very important to grow and develop the world of education. Because education does not only talk about the growth and development of students, but also has an important role in making it happen in helping to provide quality and effective education, capable of producing Indonesian human resources that are high quality, productive, creative, and have high competitive power with other nations.